Antioxidant Efficacy of Green-Synthesized Silver Nanoparticles Promotes Wound Healing in Mice - Vajravathi Lakkim; Madhava C. Reddy; VijayaDurga V. V. Lekkala; Veeranjaneya Reddy Lebaka; Mallikarjuna Korivi; Dakshayani Lomada (MDPI AG, 2023)
Developing an efficient and cost-effective wound-healing substance to treat wounds and regenerate skin is desperately needed in the current world. Antioxidant substances are gaining interest in wound healing, and green-synthesized silver nanoparticles have drawn considerable attention in biomedical applications due to their efficient, cost-effective, and non-toxic nature. The present study evaluated in vivo wound healing and antioxidant activities of silver nanoparticles from Azadirachta indica (AAgNPs) and Catharanthus roseus (CAgNPs) leaf extracts in BALB/c mice. We found rapid wound healing, higher collagen deposition, and increased DNA and protein content in AAgNPs- and CAgNPs (1% w/w)-treated wounds than in control and vehicle control wounds. Skin antioxidant enzyme activities (SOD, catalase, GPx, GR) were significantly (p < 0.05) increased after 11 days CAgNPs and AAgNPs treatment. Furthermore, the topical application of CAgNPs and AAgNPs tends to suppress lipid peroxidation in wounded skin samples. Histopathological images evidenced decreased scar width, epithelium restoration, fine collagen deposition, and fewer inflammatory cells in CAgNPs and AAgNPs applied wounds. In vitro, the free radical scavenging activity of CAgNPs and AAgNPs was demonstrated by DPPH and ABTS radical scavenging assays. Our findings suggest that silver nanoparticles prepared from C. roseus and A. indica leaf extracts increased antioxidant status and improved the wound-healing process in mice. Therefore, these silver nanoparticles could be potential natural antioxidants to treat wounds.